Best Practices for Grant Development: Starting With the Idea - Kathryn A. Stofer (EDIS)
Grant writing has become an expectation for Extension faculty at the state and county level. However, aside from a few workshops provided by the university, new faculty may feel like they have few resources to help them sharpen their practices at applying for and securing grant funding. This publication is meant to support Extension professionals, especially at the county level, in building good grant development habits.